A Reanalysis of the Black Wheel-Made Ware of the Intermediate Bronze Age. (June 2015) - Bechar, Shlomit
Abstract : The paper focuses on the distribution, typology and technology of Black Wheel-Made Ware (also known as "Megiddo Ware") and presents a discussion of its origin and date. In the second half of the third millennium BCE the southern Levant witnessed a radical change in settlement pattern, nature of sites and material-culture assemblages. One of the features defining this period was the regionalism in the ceramic repertoire. Despite varying opinions regarding the division of the pottery groups, it is agreed that one of these groups-the Black Wheel-Made Ware-was limited to northern Israel.